Generation of an induced pluripotent stem cell line (UCLi026-A) from a patient with ADCY5-related disease carrying the heterozygous variant c.1253G > A; (p. Arg418Gln) - Sharmin Alhaque; Dimitri Budinger; Barbara Garavaglia; Giovanna Zorzi; Serena Barral; Manju A. Kurian (Stem Cell Research)
Adenylyl cyclase 5 (ADCY5)-related diseases are a rare group of genetic disorders that commonly present in childhood. Heterozygous mutations in ADCY5 lead to ADCY5-related dyskinesia, comprising a wide array of disabling hyperkinetic movement disorders including chorea, myoclonus and/or dystonia. We generated an induced pluripotent stem cell line from the fibroblasts of an affected patient with the common heterozygous pathogenic variant, c.1253G > A (p.Arg418Gln). This line was further characterised for pluripotency, differentiation potential and genomic integrity. This cell line, UCLi026-A (UCL-NG-ADCY5-001) can be utilized for in vitro disease modelling of ADCY5-related diseases, as well as for the development of novel therapeutic approaches.